Peningkatan Okupansi Mes B Gereja Kalimantan Evangelis Banjarmasin Dengan Digital Marketing - Darnita, Cristi Devi; Triadi, Defri (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
The Covid-19 pandemic has caused the occupancy of Mes GKE B in Banjarmasin, South Kalimantan, to fluctuate. Business promotions that still use traditional methods cause people to be less aware of the profiles and facilities offered by the hotel. This research aims to Develop digital marketing media for the occupancy of Mes GKE B Banjarmasin; and Compare the occupancy results of Mes B GKE Banjarmasin before and after using digital marketing. The method used is R&D (Research and Development), which aims to develop and create digital marketing designs for social media types at the Mes GKE B Banjarmasin lodging business. This study data acquisition technique utilizes observation, questionnaires and documentation. The increase in occupancy is assessed using the AISAS model: Attention, Interest, Search, Action, and Share. The development results are in the form of digital marketing media designs containing business profiles and lodging facilities distributed via Instagram, WhatsApp and Facebook social media. Marketing results using digital marketing show an increase in occupancy of Mes GKE B Banjarmasin by 58% until September 2022, with a visit rate of 380 Mes GKE accounts with an average of 13 accounts visiting Instagram Mes GKE per day. Pandemi Covid 19 menyebabkan okupansi Mes GKE B di Banjarmasin, Kalimantan Selatan mengalami fluktuasi. Promosi usaha yang masih menggunakan cara tradisional menyebabkan masyarakat kurang mengetahui profil dan fasilitas hotel yang ditawarkan. Penelitian ini bertujuan untuk mengembangkan media digital marketing untuk okupansi Mes GKE B Banjarmasin; dan membandingkan hasil okupansi Mes B GKE Banjarmasin sebelum dan sesudah penggunaan digital marketing. Metode yang digunakan adalah R&D (Research and Development) yang mempunyai target mengembangkan dan membuat desain digital marketing jenis sosial media pada usaha penginapan Mes GKE B Banjarmasin. Teknik pemerolehan data studi ini memanfaatkan observasi, angket dan dokumentasi. Peningkatan okupansi dinilai menggunakan model AISAS yaitu: Attention, Interest, Search, Action, and Share. Hasil pengembangan berupa desain media digital marketing berisi profil usaha dan fasilitas penginapan yang disebarkan melalui media sosial Instagram, whatsapp dan Facebook. Hasil pemasaran menggunakan digital marketing menunjukan peningkatan okupansi Mes GKE B Banjarmasin sebesar 58% sampai dengan bulan September 2022 dengan tingkat kunjungan pada akun Mes GKE sebanyak 380 akun dengan rerata 13 akun yang mengunjungi Instagram Mes GKE per hari.